Capacity development for health research in Africa: experiences managing the African Doctoral Dissertation Research Fellowship Program - Wambugu Susan W; Izugbara Chimaraoke O; Kabiru Caroline W; Ezeh Alex C (BMC, 2010)
Abstract Africa's progress depends on her capacity to generate, adapt, and use scientific knowledge to meet regional health and development needs. Yet, Africa's higher education institutions that are mandated to foster this capacity lack adequate resources to generate and apply knowledge, raising the need for innovative approaches to enhance research capacity. In this paper, we describe a newly-developed program to support PhD research in health and population sciences at African universities, the African Doctoral Dissertation Research Fellowship (ADDRF) Program. We also share our experiences implementing the program. As health research capacity-strengthening in Africa continues to attract attention and as the need for such programs to be African-led is emphasized, our experiences in developing and implementing the ADDRF offer invaluable lessons to other institutions undertaking similar initiatives.